Động học phản ứng polyme hóa của 2-hydroxyetyl metacrylat (HEMA) và cấu trúc hình thái của poly(etyl acrylat)/HEMA blend - Đan Thủy, Văn Phạm (Vietnam Journal of Chemistry, 2015)
Reaction kinetics of 2-hydroxyethyl methacrylate (HEMA) photo-polymerization, which is the driving force of the morphology of poly(ethyl acrylate)/HEMA mixture, was monitored by using Fourier Transform Infrared Spectrometer (FTIR, Perkin-Elmer, model Spectrum GX). The photo-polymerization of HEMA was carried out under irradiation with visible light λ = 405 nm in the presence of Lucirin TPO used as an initiator. The experimental results of HEMA polymerization in the bulk state and in the mixture with poly(ethyl acrylate) (PEA) showed the dependence of reaction yield, the mean reaction rate (dφ/dt) and the characteristic time (τ) on the irradiation intensity. The presence of PEA also affects the reaction kinetics of HEMA polymerization. The molecular weight of PHEMA, the change in the viscosity of the medium, and the concentration fluctuations are important factors in the reaction kinetics of HEMA polymerization. The induced morphology of HEMA/PEA mixture was observed by Laser Scanning Confocal Microscope (LSCM) (LSM 5 Paslcal, Carl Zeiss). PEA component was labeled with Rhodamine B for fluorescence imaging using LSCM. The morphology of PEA/HEMA mixtures induced under several experimental conditions such as irradiation intensity, weight fraction of two components and crosslinker were observed and summarized in the morphology maps. The morphology of PHEMA droplets was found to disperse in PEA continuous matrix. Further discussion on the obtained morphology was discussed after the characteristic length (ξ) of the morphology was analyzed by 2D-Fast Fourier Transform (2D-FFT). The characteristic length was found to be affected by the molecular weight of PHEMA, the change in the viscosity of the medium, and the concentration fluctuations as well.